In vitro evaluation of cutaneous penetration of acyclovir from semisolid commercial formulations and relation with its effective antiviral concentration (Brazilian Journal of Pharmaceutical Sciences, 2016)
The evaluation of drug permeation/penetration of semisolid formulations into animal skin can be useful to supplement the pharmaceutical equivalence. This paper describes the in vitro assessment of acyclovir (ACV) into porcine skin from commercial formulations with etermination of drug concentration in different layers of cutaneous tissue to correlate with effective antiviral concentration in order to improve the equivalence decision. Studies were conducted using Franz cells and porcine skin. Selected pharmaceutical creams containing ACV had identical (reference and generic) and different (similar) excipients. A software program was employed for the simulation of antiviral effectiveness in the skin. Regarding ACV skin penetration, the first batch of the generic product showed a significant difference from reference and similar products, while in the second batch all products demonstrated equivalent drug penetration in the skin. Simulation studies suggest that formulations analysed exhibit a pharmacological effect even when in contact with Herpes simplex strains of high IC50 (inhibitory concentration required to reduce viral replication by 50%). According to results, it can be assumed that the in vitro cutaneous permeation/penetration study does not supply sensitivity information regarding small alterations of ACV semisolid formulations due to the variability inherent to the method, although it can be relevant to pharmaceutical equivalence studies in the development of semisolid products.